2017
DOI: 10.3389/fnins.2017.00688
|View full text |Cite
|
Sign up to set email alerts
|

Aging Induces Changes in the Somatic Nerve and Postsynaptic Component without Any Alterations in Skeletal Muscles Morphology and Capacity to Carry Load of Wistar Rats

Abstract: The present study aimed to analyze the morphology of the peripheral nerve, postsynaptic compartment, skeletal muscles and weight-bearing capacity of Wistar rats at specific ages. Twenty rats were divided into groups: 10 months-old (ADULT) and 24 months-old (OLD). After euthanasia, we prepared and analyzed the tibial nerve using transmission electron microscopy and the soleus and plantaris muscles for cytofluorescence and histochemistry. For the comparison of the results between groups we used dependent and ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
(194 reference statements)
0
3
0
Order By: Relevance
“…Since SFI is very sensitive to lesion in this nerve (16), the decreased SFI found in 24- and 30-month-old rats in the present study indicates sciatic nerve lesion. In fact, morphological changes were found in peripheral nerves of 10- and 24-month-old Wistar rats (31).…”
Section: Discussionmentioning
confidence: 99%
“…Since SFI is very sensitive to lesion in this nerve (16), the decreased SFI found in 24- and 30-month-old rats in the present study indicates sciatic nerve lesion. In fact, morphological changes were found in peripheral nerves of 10- and 24-month-old Wistar rats (31).…”
Section: Discussionmentioning
confidence: 99%
“…All outcomes analyzed in this study followed standardized criteria ( Carbone et al, 2017 ; Krause Neto et al, 2017 ; Bessaguet et al, 2018 ; Krause Neto et al, 2022b ). We took fifteen microphotographs per nerve per rodent in each group according to the protocol by Krause Neto et al (2022b) .…”
Section: Methodsmentioning
confidence: 99%
“…Recent work has suggested that the increase or absence of stimuli can elicit changes in the neuromuscular system ( Wilson and Deschenes, 2005 ; Krause Neto et al, 2017 ; Deschenes et al, 2021 ; Krause Neto et al, 2021 ; Deschenes and Stock, 2022 ; Krause Neto et. 2015 ).…”
Section: Introductionmentioning
confidence: 99%